NCOG-11. ASSOCIATION OF HYPERGLYCEMIA AND TUMOR SUBCLASS ON SURVIVAL IN IDH-WILDTYPE GLIOBLASTOMA. (12th November 2021) - Liu, Elisa; Vasudevaraja, Varshini; Sviderskiy, Vladislav; Feng, Yang; Tran, Ivy; Serrano, Jonathan; Cordova, Christine; Kurz, Sylvia; Golfinos, John; Sulman, Erik; Placantonakis, Dimitris; Possemato, Richard; et al.
Abstract: BACKGROUND: RNA expression and DNA methylation studies have identified different subclasses of isocitrate dehydrogenase (IDH)-wildtype (wt) glioblastoma (GBM). However, the prognostic significance of molecular subclasses is unclear. Although hyperglycemia has been previously associated with worse survival, attempts to lower glucose have yielded mixed responses. The role of hyperglycemia may be confounded by molecular heterogeneity and have different impact in molecularly distinct GBM subclasses. METHODS: Clinical, laboratory, and molecular data on 89 IDH-wt GBMs profiled by clinical next-generation sequencing and treated with Stupp protocol were reviewed. IDH-wt GBMs were subclassified into RTKI (Proneural), RTKII (Classical) and Mesenchymal subtypes using DNA methylation. Average glucose was calculated by time-weighting plasma glucose measurements between diagnosis and last follow-up. RESULTS: Patients were stratified into three groups using average glucose: tertile one (< 100mg/dL), tertile two (100-115mg/dL), and tertile three ( > 115mg/dL). Comparison across glucose tertiles revealed no significant differences in Karfnosky Performance Status (KPS), dexamethasone dose, MGMT methylation, or methylation subclass. Overall survival (OS) was not affected by methylation subclass (log-rank p=0.9) but decreased with higher glucose (log-rank p=0.015). Higher glucose tertiles were associated with poorer OS among RTK I (log-rank p=0.08) and mesenchymal tumors (log-rank p=0.05), but not RTK II (log-rank p=0.99). After controlling for age, KPS, dexamethasone dose, and MGMT status, glucose remained significantly associated with survival (adjusted hazard ratio=5.2, p=0.02). DNA methylation clustering did not identify a unique signature associated with high or low glucose levels. Metabolomic analysis of 23 tumors showed minimal variation across metabolites within the cohort with no differences across molecular subclasses. CONCLUSION: Higher average glucose values were associated with poorer OS in RTKI and Mesenchymal IDH-wt GBM, but not RTKII. There were no discernible epigenetic or metabolomic differences between tumors in different glucose environments, suggesting a potential survival benefit with systemic glucose lowering in selected molecular subtype.